Glucose-6-Phosphate Dehydrogenase Protects Escherichia Coli from Tellurite-Mediated Oxidative Stress - Vasquez-Guzman, C; Arenas-Salinas, F (2011)
The tellurium oxyanion tellurite induces oxidative stress in most microorganisms. In Escherichia coli, tellurite exposure results in high levels of oxidized proteins and membrane lipid peroxides, inactivation of oxidation-sensitive enzymes and reduced glutathione content. In this work, we show that tellurite-exposed E. coli exhibits transcriptional activation of the zwf gene, encoding glucose 6-phosphate dehydrogenase (G6PDH), which in turn results in augmented synthesis of reduced nicotinamide adenine dinucleotide phosphate (NADPH). Increased zwf transcription under tellurite stress results mainly from reactive oxygen species (ROS) generation and not from a depletion of cellular glutathione. In addition, the observed increase of G6PDH activity was paralleled by accumulation of glucose-6-phosphate (G6P), suggesting a metabolic flux shift toward the pentose phosphate shunt. Upon zwf overexpression, bacterial cells also show increased levels of antioxidant molecules (NADPH, GSH), better-protected oxidation-sensitive enzymes and decreased amounts of oxidized proteins and membrane lipids. These results suggest that by increasing NADPH content, G6PDH plays an important role in E. coli survival under tellurite stress. © 2011 Sandoval et al.